Tinjauan Teologis Liturgi Pemindahan Tulang Pada Pemugaran Makam Bagi Suku Dayak Kristen - Angellyna, Sri (Institut Agama Kristen Negeri Palangka Raya, 2024)
The study in this research looks at the use of grave removal liturgy in the grave removal ritual for Christians at the GKE Sinta Petuk Liti congregation. This research was conducted using a qualitative research approach with a descriptive type of research because the focus of this writing describes a research result with the aim of providing an explanation related to the phenomenon of grave removal worship using the grave removal liturgy, in which there is a bone washing ritual but carried out by Christian Dayaks. Data collection in this paper uses interviews, observation, documentation and literature study. Data analysis used in this writing includes data reduction, data presentation, and data conclusion drawing and verification. This analysis will help the author to see the theological review of the bone removal liturgy in the restoration of graves in Petuk Liti village for Christian Dayaks. The removal of graves for Christians in the GKE Sinta Petuk Liti congregation has meaning as a sign of respect and a way for families to express love for the deceased.